The role of transparency in reducing administrative corruption - عايد, صالح عبد; المنديل, ناظر احمد (Journal of Legal Sciences, 2019)
Global attention to transparency has increased following the spread of corruption in many countries. Therefore, in this study, we have to identify the concept of linguistic and constitutional transparency in order to give a clear picture of this principle. In order to achieve the proper application of transparency, we must understand the transparency and its legal basis, as well as its nature, dimensions and levels, which must be adhered to when applied in administrative work and any administrative system that seeks transparency to achieve certain objectives. We have addressed these objectives and their importance. We have demonstrated the types of transparency, as well as the study required us to clarify the requirements and constraints of the application that the management must adhere to in order to maximize the benefit of The application of this system in the conduct of public facilities, as well as a statement from the experiences of the Department of State, as well as to clarify its role in the prevention of corruption.